2022
DOI: 10.1186/s12985-022-01871-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of antigen detection rapid diagnostic test (Ag-RDT) for COVID-19 diagnosis in a primary healthcare center during the Shanghai COVID-19 quarantine period

Abstract: Background Rapid and accurate detection of SARS-CoV-2 infection is the cornerstone of prompt patient care. However, the reliability of the antigen rapid diagnostic test (Ag-RDT) in the diagnosis of SARS-CoV-2 infection remains inconclusive. Methods We conducted a field evaluation of Ag-RDT performance during the Shanghai Coronavirus disease 2019 (COVID-19) quarantine and screened 7225 individuals visiting our Emergency Department. 83 asymptomatic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This means that more social activities can be resumed through more intensive detection strategies, so that people can resume their normal lives as much as possible, while ensuring that the epidemic remains at a low level. This showed that it is necessary for the normalized testing program / regular nucleic acid testing to be maintained in order to help to restore social activities under the optimal control framework [ 50 – 52 ]. However, this was different from the case where the threshold was 10 when the threshold is too large, say 1000, then even if we keep the maximum detection rate, the social activity rate will not recover to 80%.…”
Section: Discussionmentioning
confidence: 99%
“…This means that more social activities can be resumed through more intensive detection strategies, so that people can resume their normal lives as much as possible, while ensuring that the epidemic remains at a low level. This showed that it is necessary for the normalized testing program / regular nucleic acid testing to be maintained in order to help to restore social activities under the optimal control framework [ 50 – 52 ]. However, this was different from the case where the threshold was 10 when the threshold is too large, say 1000, then even if we keep the maximum detection rate, the social activity rate will not recover to 80%.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the screening of asymptomatic patients using RAT kits is limited [ 34 ] and the sensitivity of RAT kits reduces the number of true-positive results with Ct values > 25 [ 35 , 36 ]. The primary finding of this study was that the Acrosis kit showed a high recall rate ( Table 1 ) and highly sensitive optimal cut-off Ct value of 28.57 ( Supplementary Figure S1D ) compared with the other three RAT kits ( Supplementary Figure S1A–C ).…”
Section: Discussionmentioning
confidence: 99%